Valoración de tolerancia de implantes subdérmicos versus inyectables en pacientes de edad fértil de 20 a 30 años de edad que acuden a consulta externa de Ginecología y Obstetricia en el Hospital Universitario de Motupe en el periodo marzo-agosto 2015. - Torres Leiva, Yenny María (2016)
This research aims to determine the tolerance between subdermal and injectable implants in patients aged 20 to 30 years of age. This study is descriptive, transversal, performed at the University Hospital of Motupe of Loja's city, whose universe was 210 patients and sample 30 women using the Etonogestrel subdermal implants and 30 using norethisterone enanthate injectable contraceptives more estradiol valerate, which met the criteria of inclusion and exclusion; considering the following objectives: identify the tolerance in patients using implants subdermal; Meet the tolerance in patients using injectable contraceptives and recognize the adverse effects resulting from abandonment in patients with the use of injectable and subdermal implants. The technique used was a form of data, that by means of which with information gathered from the medical records, the following results were obtained: patients using the implants presented subdermal a tolerance of 73% and 27% not tolerated it by what withdrew the contraceptive; in terms of adverse effects that presented were: headache with 13%, disorders of menstruation by 10%, pain at the site of the implant 7% and 3% the mastalgia, acne and amenorrhea; while 60% belongs to users that did not show any effect. The injectable contraceptive method; 100% of users tolerate it and continues with the same; the adverse effects include: headache 3% and disorders of menstruation 3% while 94% corresponding to patients who had no adverse effect. In conclusion, the injectable contraceptive method against the subdermal implant is best tolerated since it has less adverse effects and are not cause for removal. Keywords: tolerance, implants subdermal, injection